EXPERIMENTAL INVESTIGATION OF COIR AND COWBONE REINFORCED POLYMER COMPOSITES FOR TRICYCLE BRAKE PAD APPLICATION (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
The purpose of an automobile brake is to absorb the kinetic energy of moving parts through friction. This study investigates the formulation of brake pad material using coir and cow bone reinforced polymer composite. Three different samples were created with varying proportions of coir, cow bone, and polyester resin: S1 (5% coir, 15% cow bone, 80% resin), S2 (5% coir, 10% cow bone, 85% resin), and S3 (5% coir, 5% cow bone, 90% resin). Mechanical tests showed that S3 outperformed the others in hardness (93.90), compressive strength (94.30 N/mm²), and tensile strength (18.82 N/mm²), indicating its potential for excellent braking performance. S3 also demonstrated low water absorption (1.99%), suggesting improved resistance to water-related damage, enhancing brake pad longevity. The wear index for S2 was also favorable (0.0135), indicating its potential for durable performance. Overall, the coir and cow bone reinforced polymer composite, especially the S3 formulation, offers superior mechanical properties compared to traditional brake pad materials. This innovative composite demonstrates great potential for tricycle brake pad applications, offering improved performance, durability, and environmental resistance.